Numerical Study of Predator-Prey Model with Beddington-DeAngelis Functional Response and Prey Harvesting - Fitriah, Fira; Suryanto, Agus; Hidayat, Noor (Journal of Tropical Life Science, 2015)
A modified Leslie-Gower predator-prey model with Beddington-DeAngelis functional response and Michaelis-Menten type prey harvesting is studied. The equilibrium points of the system are investigated. To see the stability of each equilibrium point, we perform some numerical simulations. Our numerical simulations show that the extinction of prey or survival of both prey and predator are conditionally stable.